Characteristics of the asymmetric Stockbridge damper - Zondi Zakhele; Kaunda Modify; Ngonda Tiyamike (MATEC Web of Conferences, 2021)
The Stockbridge damper (tuned mass absorber) is used on overhead transmission power lines to suppress wind-induced vibrations. These power lines get exposed to various types of wind motions that cause them to vibrate and this causes fatigue failure at the suspension clamp where the maximum stress occurs. Aeolian vibration is the most common wind motion that causes fatigue and eventually, failure to transmission lines. This paper presents the study of an asymmetric Stockbridge damper. A set of experiments were conducted on the damper according to the Institute of Electrical and Electronics Engineers (IEEE) 664 standards to evaluate the characteristics of the asymmetric Stockbridge damper. The results obtained revealed that the asymmetric damper is four degrees of freedom. The results also revealed a relationship between the mass and the magnitude of the resonance frequency.